An efficient flexible membrane boundary condition for DEM simulation of axisymmetric element tests. (6th December 2017) - Khoubani, Ali; Evans, T. Matthew
Summary: The mechanical response of an assembly of particles depends on the applied boundary conditions. Robust calibration of numerical discrete systems to laboratory results is also a primary step in many studies of granular materials. In this study, a new membrane model was developed for simulating axisymmetric element tests. This membrane model uses a simple algorithm of an array of independently controlled walls and is computationally efficient. The effect of boundary flexibility on the system response was investigated by simulating a series of triaxial tests on dense and loose specimens. At the specimen scale, differences in shear strength and volume change of specimens were observed. It was shown that localization pattern depends on the applied boundary conditions. At the particle scale, particle‐membrane contact forces, coordination number, local void ratio, and anisotropy of fabric were all affected by the boundary flexibility.